Efficacy of Internet-Based Guided Treatment for Genito-Pelvic Pain/Penetration Disorder: Rationale, Treatment Protocol, and Design of a Randomized Controlled Trial - Zarski, Anna-Carlotta; Berking, Matthias; Ebert, David Daniel (Frontiers in Psychiatry, 2018)
Introduction: Genito-Pelvic Pain/Penetration Disorder (GPPPD) not only adversely affects women’s sexuality and sexual satisfaction, but is also associated with a wide range of psychosocial consequences such as reduced quality of life and well-being, mental health comorbidities, and relationship distress. Evidence for effective treatment options is scarce. Aim: This paper describes the rationale, treatment protocol, and study design for a randomized controlled trial examining the efficacy of an internet-based guided intervention for GPPPD. Method: Two hundred women who meet the criteria for GPPPD and have not been able to experience sexual intercourse for at least 6 months will be recruited and randomly assigned either to the intervention group (IG) or a 6-month waitlist control group (WCG). Assessments take place at baseline (T1), peri-treatment after completion of Session 5 in IG (T2), after completion of Session 8 (T3), and after 6 months (T4). Data will be analyzed on an intention-to-treat and a completer basis. Main outcome measures: The primary outcome will be sexual intercourse involving the insertion of the partner’s penis at post-treatment. Secondary outcomes include, e.g., improved non-intercourse penetration, sexual functioning, dyadic stress coping, reduced fear of sexuality and negative penetration-related cognitions. Fear of sexuality, penetration-related cognitions, and exercise intensity will be assessed as mediators of intercourse in the IG. Sexual dysfunctions of partners will be measured at baseline (T1) and investigated as a potential moderator of the primary treatment outcome. Discussion: Given the burden associated with GPPPD and the need for specialized treatment, there is a surprising lack of evidence-based treatment options. This study aims to assess whether internet-based interventions could contribute to closing this treatment gap. Trial Registration: German Register of Clinical Studies (DRKS): DRKS00010228